2007
DOI: 10.14214/sf.296
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ground substrate on establishment of reindeer lichen after artificial dispersal

Abstract: Methods to improve the recovery of reindeer lichen after soil disturbance or overgrazing are being sought for areas where reindeer are herded. The effects of four substrates -mineral soil, moss, twigs and pine bark -on the establishment of lichen fragments after total removal of the vegetation were thus studied in a middle-aged pine stand and a clear-cut, both located in a lichen-rich pine-heath. Cladina mitis fragments of two sizes were manually dispersed in 1 m 2 quadrats and their movements from their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…A study by Lidén et al (2005) showed that new populations of arboreal lichens can be successfully established, and that existing lichen populations can be enlarged, by transplanting small fragments into suitable habitats. Furthermore, Roturier et al (2007) suggest that artificial dispersal of reindeer lichen on an appropriate substrate could be a successful strategy for promoting lichen recovery. In addition, natural colonization of reindeer lichens can be enhanced by providing substrates onto which lichen fragments can attach.…”
Section: Reducing the Effects Of Forestry On Winter Resourcesmentioning
confidence: 99%
“…A study by Lidén et al (2005) showed that new populations of arboreal lichens can be successfully established, and that existing lichen populations can be enlarged, by transplanting small fragments into suitable habitats. Furthermore, Roturier et al (2007) suggest that artificial dispersal of reindeer lichen on an appropriate substrate could be a successful strategy for promoting lichen recovery. In addition, natural colonization of reindeer lichens can be enhanced by providing substrates onto which lichen fragments can attach.…”
Section: Reducing the Effects Of Forestry On Winter Resourcesmentioning
confidence: 99%
“…Cladonia sub-genus Cladina propagates through thallus fragmentation which is an asexual mode of reproduction. Fragments are distributed naturally by wind, water and animals (Goward 2000, Brodo et al 2001, and most often fall within one metre of the colony (Heinken 1999, Roturier et al 2007. In instances where there is a large disturbance footprint, and no lichen propagules are present, lichen establishment is dispersal-limited.…”
Section: Introductionmentioning
confidence: 99%
“…In instances where there is a large disturbance footprint, and no lichen propagules are present, lichen establishment is dispersal-limited. Terrestrial lichen transplanting techniques have been examined in a variety of landscapes from red-stemmed feathermoss colonies (Cichowski et al 2008), re-generating second growth forests (Roturier et al 2007, Roturier and Bergsten 2009, Duncan 2011, handfelled and partial cut forest (Enns 1998), to quarries (Campeau 2013), mine overburden (Rapai et al 2016), aggregate mines (Hugron et al 2013), and other industrial disturbances (Turner et al study in Duncan 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations